Digital elixir? The Aakash tablet as a social innovation in information and communication technology for development (ICT4D). Issue 2 (22nd October 2021) - Abraham, John; Geobey, Sean
Abstract : Purpose: The Aakash tablet was developed as a social innovation (SI) to transform India's higher education sector. This paper aims to explain the failure of the Aakash tablet beyond the typical explanations of deficiencies in the device's technical capabilities. This paper argues that an SI lens provides a stronger explanation for its failure than the standard analyses built primarily on the technological viability of the device. Design/methodology/approach: The Aakash project ran from 2010 to 2015. During this period, a number of government and policy reports as well as mainstream media articles were published on the device. Since 2015, a number of academic articles have been published on the Aakash emphasizing its failure as a technological solution. The authors draw on these sources to frame an understanding of the Aakash's failure informed by SI theory. Findings: Through a complexity-informed analysis, the authors show that the failure of the Aakash stemmed from flawed assumptions and a failure of the initiative to engage with both the particular and constantly changing features of the broader landscape of needs and opportunities. Originality/value: This study draws attention to failure as a legitimate aspect of the study of SI. In presenting a "counter-case" to the usual success stories, it shows that the SI lens can also explain why an SI does not take off. It thereby adds to the literature on SI and complexity theory through an exploration of the complex interactions among public policy goals, technological advancements and entrepreneurship.